Pengaruh Kebijakan Moneter Terhadap Jumlah Uang Beredar Dalam Menjaga Stabilitas Ekonomi Di Indonesia - Lubis, Isman; Siregar, Zulkifli; Rahmarisa, Faty (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2025)
This research focuses on the economic conditions and the money supply in Indonesia over the past five years, as well as the policies to be issued by Bank Indonesia. The objective of this research is to analyze the impact of monetary policy on the money supply and its role in maintaining economic stability in Indonesia. The object of the research is the monetary policy implemented by Bank Indonesia, as well as its influence on the money supply and economic stability. The method used in this research is qualitative descriptive, with the collection of secondary data through information obtained from the official website of Bank Indonesia and the Central Statistics Agency. The results of the research indicate that the monetary policy implemented by Bank Indonesia plays a significant role in maintaining economic stability and the money supply